2016
DOI: 10.1097/bsd.0b013e31828ffc54
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cervical Discectomy and Fusion for Adjacent Segment Disease

Abstract: Performing ACDF for ASD resulted in significant improvements in patient pain, disability, and quality of life. Further, the mean 2-year cost-per-QALY was determined to be $60,526, which suggests surgical intervention to be cost effective. This study is the first to provide evidence that performing an ACDF for ASD is both clinically and cost effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Patients with acute or subacute neurological changes and invalid conservative treatment should be treated with further surgery. Revision surgery for symptomatic ASD was reported to be required in 5.1% and 22.2% of cases [ 3 , 4 , 7 9 ] and can be performed by second anterior fusion (ACDF or ACCF) [ 7 , 10 , 11 ], laminoplasty [ 12 ], posterior repeat cervical fusion [ 18 ], or artificial disc replacement [ 13 , 14 ]. However, two-level ASD is a special type of ASD that is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients with acute or subacute neurological changes and invalid conservative treatment should be treated with further surgery. Revision surgery for symptomatic ASD was reported to be required in 5.1% and 22.2% of cases [ 3 , 4 , 7 9 ] and can be performed by second anterior fusion (ACDF or ACCF) [ 7 , 10 , 11 ], laminoplasty [ 12 ], posterior repeat cervical fusion [ 18 ], or artificial disc replacement [ 13 , 14 ]. However, two-level ASD is a special type of ASD that is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, two-level ASD is a special type of ASD that is rarely reported. O'Neill et al [ 11 ] retrospectively reviewed 40 patients who underwent ACDF for ASD and described that ASD occurred at both adjacent levels in 10% of cases. Lee et al [ 8 ] analyzed 78 patients who required reoperation for ASD and found that 16 patients (20.5%) underwent treatment at both cephalad and caudal segments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anterior cervical discectomy and fusion (ACDF) is the gold-standard surgical treatment for cervical degenerative disc disease. 1 One of the main complications of ACDF is the development of adjacent segment degeneration (ASD) and adjacent segment disease, which occurs when fusion of cervical spinal segments limits their range of motion (ROM) and increases intradiscal pressure of the adjacent intervertebral discs. 2 One alternative procedure is cervical total disc replacement (CTDR), theoretically preserving the ROM of spinal segments and minimize the risk of ASD.…”
Section: Introductionmentioning
confidence: 99%